Archaeological science meets Māori knowledge to model pre-Columbian sweet potato (Ipomoea batatas) dispersal to Polynesia’s southernmost habitable margins - Barber, Ian G.; Higham, Thomas F. G. (PloS one, 2021)
Most scholars of the subject consider that a pre-Columbian transpacific transfer accounts for the historical role of American sweet potato Ipomoea batatas as the kūmara staple of Indigenous New Zealand/Aotearoa Māori in cooler southwestern Polynesia. Archaeologists have recorded evidence of ancient Polynesian I . batatas cultivation from warmer parts of generally temperate-climate Aotearoa, while assuming that the archipelago’s traditional Murihiku region in southern South Island/Te Waipounamu was too cold to grow and store live Polynesian crops, including relatively hardy kūmara . However, archaeological pits in the form of seasonal Māori kūmara stores ( rua kūmara ) have been discovered unexpectedly at Pūrākaunui on eastern Murihuku’s Otago coast, over 200 km south of the current Polynesian limit of record for premodern I . batatas production. Secure pit deposits that incorporate starch granules with I . batatas characteristics are radiocarbon-dated within the decadal range 1430–1460 CE at 95% probability in a Bayesian age model, about 150 years after Polynesians first settled Te Waipounamu. These archaeological data become relevant to a body of Māori oral history accounts and traditional knowledge ( mātauranga ) concerning southern kūmara , incorporating names, memories, landscape features and seemingly enigmatic references to an ancient Murihiku crop presence. Selected components of this lore are interpreted through comparative exegesis for correlation with archaeological science results in testable models of change. In a transfer and adaptation model, crop stores if not seasonal production technologies also were introduced from a warmer, agricultural Aotearoa region into dune microclimates of 15th-century coastal Otago to mitigate megafaunal loss, and perhaps to support Polynesia’s southernmost residential chiefdom in its earliest phase. A crop loss model proposes that cooler seasonal temperatures of the post-1450 Little Ice Age and (or) political change constrained kūmara supply and storage options in Murihiku. The loss model allows for the disappearance of kūmara largely, but not entirely, as a traditional Otago crop presence in Māori social memory.